EVALUATION OF ANTIBACTERIAL ACTIVITY OF ESSENTIAL OIL OF CINNAMOMUM ZEYLANICUM, EUGENIA CARYOPHYLLATA, AND ROSMARINUS OFFICINALIS AGAINST STREPTOCOCCUS ORALIS - Hsaine, Samira; Charof, Reda; Ounine, Khadija (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Streptococcus oralis plays an important role in the biofilm formation of dental plaque and the occurrence of periodontal disease. The present study was conducted to evaluate in vitro antibacterial activity of three essential oils, namely, Cinnamomum zeylanicum, Eugenia caryophyllata, and Rosmarinus officinalis against S. oralis. Methods: The antibacterial activity of essential oils was investigated by diffusion method using sterile discs (or aromatograms). The minimum inhibitory concentration (MIC) of essential oils showing important antibacterial activity was measured using the broth dilution method. Results: Evaluation of the antibacterial activity of three essential oils as determined by the aromatogram technique showed that the essential oil of R. officinalis had no effect on S. oralis, while the latter was extremely sensitive to the other two essential oils, but with a higher efficiency of the essential oil of C. zeylanicum (42 mm diameter) than E. caryophyllata (20 mm diameter). Similarly, the MIC and minimum bactericidal concentration (MBC) were higher for the essential oil of C. zeylanicum than the essential oil of E. caryophyllata. The MBC/MIC ratio is of the order of 2. The essential oils studied therefore appear to exert bactericidal activity against S. oralis. Conclusion: The findings suggest that essential oils of C. zeylanicum and E. caryophyllata may be used as an alternative to synthetic antibiotics. Â